Implementation of Non-Formal Educational Learning Activities at the Abituren Mustafawiyah Sanggar Family Tutoring Malaysia - Adri, Helmia Tasti; Suwarjono, Suwarjono; Ridwan, Muhammad; Kusnaedi, Tithania (Education Achievement: Journal of Science and Research, 2025)
This research is motivated by the high interest and attendance of students in participating in the implementation of learning activities at the Abituren Mustafawiyah Family Tutoring Studio. This study aims to determine the implementation of Non-Formal Education learning activities at the Mustafawiyah Abituren Family Tutoring Studio Malaysia. Qualitative research approach with case study research type. Case studies are conducted to be carried out intensively, in detail and in depth on the implementation of learning activities at the Abituren Mustafawiyah Family Family Guidance Studio . The data collection techniques used were observation, interviews and documentation obtained from the community at the Abituren Mustafawiyah Family Tutoring Studio. Data were analyzed by reducing relevant data, presenting data, and drawing conclusions. The results of this study indicate that the implementation of learning activities at the Abituren Mustafawiyah Family Family Tutoring Studio runs well by using game methods such as playing characters and utilizing learning media, especially audio-visual media.